Telepresent Focused Assessment With Sonography for Trauma Examination Training Versus Traditional Training for Medical Students: A Simulation‐Based Pilot Study. (1st February 2018) - Poland, Scott; Frey, Jennifer A.; Khobrani, Ahmad; Ondrejka, Jason E.; Ruhlin, Michael U.; George, Richard L.; Gothard, M. David; Ahmed, Rami A.
Abstract : Objectives: Telepresent education is becoming an important modality in medical education, as it provides a means for instructors to lead education sessions via videoconferencing technologies. This study aimed to compare the effectiveness of telepresent ultrasound training versus traditional in‐person ultrasound training. Methods: Medical student cohorts were educated by either traditional in‐person instruction or telementoring on how to perform a focused assessment with sonography for trauma (FAST) examination. Effectiveness was evaluated by pre– and post–multiple‐choice tests (knowledge), confidence surveys, and summative simulation scenarios (hands‐on FAST simulation). Formative simulation scenario debriefings were evaluated by each student using the Debriefing Assessment for Simulation in Healthcare student version (DASH‐SV). Results: Each method of instruction had significant increases in knowledge, confidence, and hands‐on FAST simulation performance ( P  < .05). The collective increase in knowledge was greater for the in‐person group, whereas the improvement in FAST examination performance during simulations was greater for the telementored group. Confidence gains were comparable between the groups. The DASH‐SV scores were significantly higher for the in‐person group for each criterion; however, both methods were deemed effective via median scoring. Conclusions: Telepresent education is a viable option for teaching the FAST examination to medical students.